2000
DOI: 10.1021/jp000338f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Effect on Macroscopic Chirality Modification of Cholesteric Mesophases by Photochromic Azobenzene Dopants

Abstract: Azobenzenes having different positional substituents were dissolved in cholesteric liquid crystals to make cholesteric pitches tunable by photoisomerization. E-to-Z photoisomerization of 3,3‘-disubstituted or 2,2‘-dimethyl-3,3‘-disubstituted azobenzenes resulted in a moderate change or even no change in the maximum wavelengths of reflectivity of the cholesteric phase, whereas azobenzene or 4,4‘-disubstituted azobenzenes showed much bigger changes. The difference in the conformations between the E- and Z-isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…[3,4] The sensitivity of ChLCs to external parameters, such as temperature, the presence of impurities, and light, has led to many practical applications and has been the subject of much theoretical research. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several mechanisms have been proposed to explain the role that the dopant molecules play in the modulation of the macroscopic chirality of ChLCs. [11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] The sensitivity of ChLCs to external parameters, such as temperature, the presence of impurities, and light, has led to many practical applications and has been the subject of much theoretical research. [2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Several mechanisms have been proposed to explain the role that the dopant molecules play in the modulation of the macroscopic chirality of ChLCs. [11,[24][25][26][27][28] Recently, we reported that the mechanism of the helical-pitch shift that is induced by achiral dopants (as well as in dimesogenic compounds) is due to enhancement of smectic A (SmA)-like clusters in the cholesteric phases.…”
Section: Introductionmentioning
confidence: 99%
“…This twisting can act as an obstruction to kinetically trap disclination lines and prevent the otherwise favourable shortening and merging process. The distance over which the director turns by 2p, known as the intrinsic cholesteric pitch p 0 , can be controlled by temperature 22 , optical illumination 23 or chiral dopants 24 . The periodic modulation of the average orientation effectively changes the optical axis, achieving specific optical characteristics of cholesterics.…”
mentioning
confidence: 99%
“…Sackmann showed that selective photoswitching of light reflection, resulting in color changes, can be obtained with a ChLC doped with azobenzene, [11] Witte et al used a menthone derivative, [12][13][14] while Shibaev reported a photochromic copolymer of both azobenzene and menthone derivatives. [15][16][17] In addition, a relationship between molecular structure and HTP of a chiral compound and control of helical structure was reported by Ichimura et al [18][19][20] Azobenzene systems represent very attractive phototriggers in Ch media, thanks to their resistance to photofatigue, the simplicity of the molecules, and the ease of modification of their molecular structures.…”
Section: Introductionmentioning
confidence: 94%